Spreminjanje podnebja ter človekovo zdravje in počutje - Cegnar, Tanja (Geografski vestnik, 2005)
The world's climate system is an integral part of the complex of life-supporting environment. Climate and weather have always had a powerful impact on human health and well-being. The global climate system is coming under pressure from human activities. Environmental quality is crucial for human health. Global climate change will affect human well-being and health in several ways, there will be direct and indirect impacts. Thermal complex is the most important among different impacts of atmosphere on human beings, but also ozone depletition, air pollution, severe weather, vector, food and water born diseases should be considered. Impacts of climate change on food production, fresh water availability and migrations will also have impact on human health and well-being.
Keywords: climatology; klimatologija; climate; podnebje; vreme; weather; biometeorologija; klimatske spremembe; podnebne spremembe; kvaliteta življenja